(untitled) (Journal of Atomic and Molecular Sciences, 2011)
We have studied the intensity squeezing of superposition state of excited coherent states and proposed a new method to prepare superposition state of excited coherent states of vibrational motion of trapped ion. This method is based on the interaction of a single trapped ion with two traveling wave light fields with different frequencies. An obvious merit of this method is that it works without application of the perturbation theory.